Euchlorocystis gen. nov. and Densicystis gen. nov., Two New Genera of Oocystaceae Algae from High‐altitude Semi‐saline Habitat (Trebouxiophyceae, Chlorophyta). (28th August 2017) - Liu, Xudong; Zhu, Huan; Song, Huiyin; Wang, Qinghua; Xiong, Xiong; Wu, Chenxi; Liu, Guoxiang; Hu, Zhengyu
Abstract: The Oocystaceae family is generally considered to contain common freshwater eukaryotic microalgae, and few are reported living in semi‐saline habitats. Our latest ecological survey in Qinghai Lake and Angzicuo Lake, both large, closed, high‐altitude, semi‐saline lakes located on the Qinghai‐Tibet plateau in China, revealed Oocystaceae species as a dominant group among plankton. Since limited knowledge exists about semi‐saline species in the Oocystaceae family, a taxonomical study was carried out using morphological and phylogenetic methods. Using this approach, four new strains of Oocystaceae were identified and successfully cultured in the lab. Molecular results correlated with morphological characters and resolved these species into at least three genera. A new genus, Euchlorocystis, with type species Euchlorocystis subsalina, is described here as having the distinctive morphology of multiple pyrenoids per chloroplast among Oocystaceae, and an independent phylogenetic position at the base of the Oocystaceae. Similarly, the genus Densicystis, with type species Densicystis glomerata, is newly proposed here as having a unique colony morphology of dozens or hundreds of little cells tightly embedded in ellipsoid to round mucilage masses. Oocystis marina, originally described from the Baltic Sea, was also identified in Qinghai Lake and Angzicuo Lake and phylogenetically positioned in the semi‐saline clade of the Oocystaceae. The result that a marine species was detected in the closed inland lakes implies a further need to reevaluate the origins of these species.